2006 IEEE Conference on Computer Aided Control System Design, 2006 IEEE International Conference on Control Applications, 2006 2006
DOI: 10.1109/cacsd-cca-isic.2006.4776986
|View full text |Cite
|
Sign up to set email alerts
|

Predictive control of earth station antenna with backlash compensation

Abstract: In this paper, Generalized Predictive Control (GPC) algorithm is implemented to control an earth station antenna. Nonlinear term in motors caused by gearbox or other parts is modeled by a backlash block. Simulation results show the effectiveness of GPC method for robust control in the presence of backlash nonlinearity without a priori knowledge about upper and lower bounds of backlash. Also, adaptation mechanism as a self tuning predictive control is used to conquer environment changing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…However, an explicit solution to a MPC problem, which was obtained offline, applies this control scheme only for a linear time-invariable (LTI) system or a piecewise affine (PWA) system [14]. Mohammadzaman et al [15] showed the effectiveness of a generalized predictive control (GPC) algorithm for robust control in the presence of backlash non-linearity without a priori knowledge of upper and lower bounds of backlash. In addition, backlash compensation using neural network and fuzzy logic have been used in feedback control systems [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, an explicit solution to a MPC problem, which was obtained offline, applies this control scheme only for a linear time-invariable (LTI) system or a piecewise affine (PWA) system [14]. Mohammadzaman et al [15] showed the effectiveness of a generalized predictive control (GPC) algorithm for robust control in the presence of backlash non-linearity without a priori knowledge of upper and lower bounds of backlash. In addition, backlash compensation using neural network and fuzzy logic have been used in feedback control systems [16,17].…”
Section: Introductionmentioning
confidence: 99%